Academic adaptation: the experience of Malay Muslim postgraduate students - Siti Salina Abdullah; Hamidah Sulaiman (penerbit ukm, 2014)
This qualitative study aimed to explore the academic experiences and coping strategies among Malay Muslim postgraduate students in Australia. The research participants were thirteen Malaysian Malay Muslim postgraduate students (9 females, 4 males) studying in a university in South Australia. They were either undergoing their Master or PhD degrees. The findings show that as international students, the Malaysian Malay Muslim postgraduate students had difficulties adjusting themselves to their new learning culture. In order to cope with the situation, they became active learners in academic areas, made changes and sought assistance in their daily lives through their spouse, other Malaysian friends or university colleagues. Maintaining faith was also frequently mentioned as one of their coping strategies.